Pembuatan Alat Bantu Kerja Pneumatik Pelepas Rubber Journal Spring Pada Bogie K5 - Henry Widya Prasetya; Akbar Zulkarnain; Diki Wahyu Arobi (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2023)
One of the facility maintenance performed on the bogie is removing the rubber journal spring. The removal of the rubber journal spring is still done manually, namely slamming it to the floor using a long bolt of about 10 cm which is inserted into the hole in the rubber journal cap to push the rubber so that it can be released from the hat within 8-10 minutes. This research was conducted to innovate tools with the aim of facilitating the maintenance process, shorter time and guaranteed safety in removing the rubber journal spring. The manufacturer of this release tool uses a pneumatic system with the components used in the form of a cylinder with a diameter of 100 mm × 200 mm in length, a 4/2 pust button valve, an air filter, a manometer, and an 8 mm air hose. From the test results, the rubber journal spring removal tool on bogie K5 using a pneumatic system requires 1.2 minutes with a pressure of 5 bar to release 1 rubber journal spring. This tool has dimensions weighing 40 kg, length 50 cm, width 30 cm, height 90 cm. Keyword: rubber journal spring, bogie, pneumatic